NILAI-NILAI AL-QUR’AN SEBAGAI MEDIASI KETEGANGAN ANTARA SAINS DAN AGAMA - Fauzi, Ahmad (Jurnal Bestari, 2003)
The suspense between science and religion happen when modern science paradigm inclared positivistic,materialistic and empiric as well as warding off to the something metaphysic characteristic that become a single strength which dominates the entire modern human thingking.The standard of the truth reduced as accurate from coherence and correspondence side.So something supra empirical and metaphysical then refused with idea that it cannot be proved in reality.Meanwhile,world phenomenon or there are so many paradigm happen that cannot be explained with modern science concept.Here,the urgent of alternative value formulation as a strain media between science and religion.Thus,this formula is will be as a basic epistemologies in improving Islam society that based on science and technology treatment which friendly environment and society.